Manfaat Asam Salisilat dalam Meningkatkan Pertumbuhan Tanaman Berdasarkan Perspektif Sains dan Islam - Aprisilia, Wanda; Fahruddin, M. Mukhlis (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2025)
The universe created by Allah SWT is a blessing that must be preserved and safeguarded. Humans, as stewards on Earth, bear the responsibility of maintaining and managing nature by avoiding destructive actions. Efforts to support environmental sustainability include the use of salicylic acid in appropriate doses to enhance plant growth while preserving the environment. The method used in this study is library research, which relies on collecting data from various literature sources. The data utilized originates from academic references such as related scientific journals, reference books, and other relevant documents. From an Islamic perspective, the use of salicylic acid can be integrated with Qur'anic teachings that emphasize the importance of environmental preservation and the avoidance of harm, as exemplified in Surah Al-A'raf (7:56), Surah Al-Baqarah (2:11), and Surah Al-A'raf (7:85). Principles of environmental preservation are also reflected in the values and practices of Sufism, including zuhd, dzikr and fikr, and hubb. Thus, these teachings encourage humanity to remain attentive to the environment and take responsibility for restoring any damage that has occurred.